Genetic legacy of southern Middle Siberian mountain and foothill populations of Scots pine (Pinus sylvestris L.): Diversity and differentiation - Sheller, Marina; Tóth, Endre György; Ciocîrlan, Elena; Mikhaylov, Pavel; Tatarintsev, Andrey; Kulakov, Sergey; Kulakova, Nadezhda; Melnichenko, Natalia; Ibe, Aleksey; Sukhikh, Tatyana; Curtu, Alexandru Lucian (Frontiers in Forests and Global Change, 2023)
Scots pine (Pinus sylvestris L.) is a widespread and economically important tree species in Eurasia. Southern Siberian, Scots pine mountain and foothills forests are especially valuable natural objects that help to stabilize environmental conditions. Due to the associated impact of natural and anthropogenic factors, the habitats of the species in southern Siberia are constantly shrinking. In this regard, the study of genetic diversity and structure of Scots pine forests in southern Siberia is very relevant. Here, we studied the genetic diversity and structure of eight Scots pine populations located in southern Middle Siberia (Russia). A high level of genetic diversity (HE = 0.518) was detected in the studied populations. No recent bottleneck effect, isolation by distance or isolation-by-environment were detected. Most genetic diversity was found within populations, while only 7% of genetic diversity occurred among populations. Both STRUCTURE analysis and UPGMA clustering showed two genetic groups. Two populations from the Minusink basin and a population from the Western Sayan Mts. formed the first group and the second group was composed of the other populations from Kuznetsk Alatau Mts., Central Tuva basin and Todzha basin. Our findings suggest that the studied Scots pine populations originate from different gene pools. The pattern of genetic diversity revealed by our study may be useful for the elaboration of conservation measures of genetic resources of Scots pine in southern Middle Siberia.